Influence of Family Environment and Consumptive Behavior Against Financial Literacy in Students - Meri Togari Maria N; Muhadjir Anwar (Economos : Jurnal Ekonomi dan Bisnis, 2022)
Financial literacy is important for society, especially students. This increase in financial literacy is expected to contribute to financial system stability. This study aims to see whether there is an influence of the family environment and consumptive behavior on financial literacy of Management Students in UPN “Veteran” Jawa Timur. In this study using quantitative methods. The population in this study were Management Students of UPN “Veteran” Jawa Timur from 2018 to 2021 period. Using a proportionate stratified random sampling technique, 101 management students were found as samples. The method of collecting research data was by distributing questionnaires. The final results of this study indicated that the family environment variable had a positive and significant influence on financial literacy, the family environment variable had a positive and significant influence on consumptive behavior, and the consumptive behavior variable had a positive but not significant effect on financial literacy.